The Friction Coefficient of Cohesive Soils and Geotextile: An Approach Based On the Direct Shear Test Data - Puri, Anas (JURNAL SAINTIS, 2017)
The soil reinforcement designing by using geotextile requires the friction coefficient of soil-geotextile interface, both granular and cohesive soils. For cohesive soils, this coefficient was usually defined by [⅔ tan f]. Is this approach efficient enough or conservative? This paper presents an approach to determine the friction coefficient of soil-geotextile interface based on the empirical data from some researchers. It was used direct shear test data on cohesive soil-geotextile interfaces. Result show that the friction coefficient of soil-geotextile interface higher than the value of tan f. It was also proved by the interface friction angle d tend to higher than the soil internal friction angle f. Hence, the approach by [⅔ tan f] would be yield excessive safety design, which the safety factor would be added for soils and geotextiles. The new approach in determining the interface friction coefficient was conducted by using direct relationship between interface friction coefficient and soil internal friction angle.